2021
DOI: 10.12968/bjon.2021.30.6.s4
|View full text |Cite
|
Sign up to set email alerts
|

Stoma formation as a palliative procedure: the role of the clinical nurse specialist in maintaining quality of life

Abstract: More than half of patients diagnosed with colon cancer present at an advanced stage, and palliative treatment may involve stoma formation. A literature review was undertaken to determine the potential effects of stoma formation as a palliative procedure on a patient's quality of life, and to examine the role of the clinical nurse specialist in this situation. Limited literature was found on this specific subject, so established evidence surrounding stoma formation and quality of life was examined in relation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…The seven included papers were published in the UK between 2003 and 2021 (Table 2). There were three guidelines (ASCN 2018, RCN 2003, two narrative reviews (McGrath 2017, Skingley 2004), a case study (Comb 2003) and a literature review (Henbrey 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seven included papers were published in the UK between 2003 and 2021 (Table 2). There were three guidelines (ASCN 2018, RCN 2003, two narrative reviews (McGrath 2017, Skingley 2004), a case study (Comb 2003) and a literature review (Henbrey 2021).…”
Section: Resultsmentioning
confidence: 99%
“…These results, however, may have been influenced by the nature of the publications. Henbrey (2021) for example, focussed only on the role of the CNS Stoma Care in palliative care. Palliative care is only a small part of most CNS Stoma Care roles, as many people live a long life with their stoma.…”
Section: Advanced Clinical Practicementioning
confidence: 99%
“…Os enfermeiros devem dedicar-se ao planejamento e execução de atividades de educação em saúde, em razão das pessoas com estomias intestinais necessitarem de orientações sobre os cuidados, e, portanto, serem treinadas e acompanhadas para o uso e o aproveitamento adequado dos recursos disponíveis e, assim, prevenir complicações, garantindo a qualidade de vida após a cirurgia 9 .…”
Section: Introductionunclassified
“…1 Systematic literature reviews and intervention studies have found several beneficial outcomes of CNS-provided care. These include enhanced quality of life with lower complication rates, 9,10 reduced length of stay and the number of readmissions in hospitals, 11,12 support for early recovery, 13 improved physical and psychological well-being of patients, improved quality of care and access to supportive care through collaborative management 10,11 as well as improved patient satisfaction, and reduction in medication errors. 11 However, a systematic review of controlled trials found inconsistent results of CNS-provided care, due to small sample sizes and failure of true randomization of patients.…”
mentioning
confidence: 99%